Show Me Small-Town Missouri - McCandless, Jake (Indiana University Press, 2020)
Where was Mark Twain born? What city has claim to a president who was only president for a day? Who has the best paddling trips in the Ozarks? What about the World's Largest Gift Store? Find these answers and more in Show Me Small-Town Missouri .Award-winning author Jake McCandless, a lover of small towns and adventures, traveled the state in search of amazing local experiences to share this treasure trove of what you can find in often-overlooked towns across Missouri. Featured are 90 sparkling gems found in all four of the state's geographical regions-the Northern Prairie, the Southwest Osage Plain, the Ozarks, and the Bootheel Lowlands. The must-see attractions, activities, restaurants, sweet shops, specialty shops, and unique vacation spots are showcased in full-color images with an easy-to-follow index to help you plan your trip.From galleries to hiking trails, candy factories to wineries, lakeside attractions to the best fireworks displays, Show Me Small-Town Missouri has everything you need to know for a day, weekend, or week full of fun.